Competency and Work Environment on Employee Performance with Internal Communication Mediation - Fakar Nur Halim; Istiatin Istiatin; Sudarwati Sudarwati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine and analyze the influence of competence and work environment on employee performance with internal communication as a mediating variable at the Surakarta Religious Court. This study uses a quantitative approach with descriptive methods. The population in this study were all 40 employees of the Surakarta Religious Court. The sampling technique used a saturated sampling method, so that the entire population was used as research respondents. Data collection was carried out through questionnaires, observation, documentation, and interviews. Data analysis used the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software through outer model testing, inner model testing, hypothesis testing, and mediation testing. The results of the study indicate that competence, work environment, and internal communication have a positive and significant effect on employee performance. Competence and work environment also have a positive and significant effect on internal communication. In addition, internal communication has been proven to mediate the influence of competence and work environment on employee performance. This indicates that improving employee performance is not only influenced by competency and work environment factors directly, but is also strengthened through effective internal communication within the organization.